Nasal lavage VEGF and TNF‐α levels during a natural cold predict asthma exacerbations. Issue 12 (December 2014) - Manthei, D. M.; Schwantes, E. A.; Mathur, S. K.; Guadarrama, A. G.; Kelly, E. A.; Gern, J. E.; Jarjour, N. N.; Denlinger, L. C.
Summary Background Asthma exacerbations contribute to significant morbidity, mortality and healthcare utilization. Furthermore, viral infections are associated with asthma exacerbations by mechanisms that are not fully understood. Objective The aim of this analysis was to determine whether cytokine patterns in patients with colds could identify risks for subsequent asthma exacerbations. Methods We analysed cytokine levels in nasal lavage fluid (NLF) in 59 subjects (46 with asthma) with acute upper respiratory symptoms and after symptomatic resolution. Analyte choice was based on potential relevance to asthma exacerbations: antiviral (IFN‐α, IFN‐β, IFN‐γ, IFN‐λ1, IP‐10, TRAIL), cell recruiting (G‐CSF, IL‐1β, IL‐8, MCP‐1, MCP‐3, TNF‐α), polarizing (CXCL13, IL‐10, IL‐13, IL‐17, TSLP), and injury remodelling (fibronectin, IL‐33, MMP‐9, VEGF). Results The overall cytokine response induced during viral infections was not different between asthmatic and non‐asthmatic individuals for a wide array of cytokines. However, mean levels of VEGF, TNF‐α and IL‐1β were 1.7‐, 5.1‐ and 4.7‐fold higher in samples from asthma subjects who exacerbated in the first 3 weeks of the cold compared with those who did not exacerbate (P = 0.006, 0.01, 0.048, respectively). Using receiver operating characteristic curve‐defined thresholds, high VEGF and TNF‐α levels predicted a shorter time‐to‐exacerbation after NLF sampling (25% exacerbation rate: 3 vs. 45 days, and 3 vs. 26 days; P = 0.03, 0.04, respectively). Conclusion and Clinical Relevance Although they produce similar cytokine responses to viral infection as non‐asthmatics, asthmatics with higher levels of VEGF and TNF‐α in NLF obtained during acute cold phases predicted subsequent asthma exacerbations in this cohort of patients with mild‐to‐moderate disease. In the future, stratifying the risk of an asthma exacerbation by cytokine profile may aid the targeting of personalized treatment and intervention strategies.